2019
DOI: 10.3390/ijerph16183248
|View full text |Cite
|
Sign up to set email alerts
|

The Most Effective Amount of Forward Movement for Oral Appliances for Obstructive Sleep Apnea: A Systematic Review

Abstract: This systematic review clarifies the amount of effective protrusion in mandibular advancement devices of oral appliances required for obstructive sleep apnea (OSA). The systematic review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Review Manager 5 and GRADEpro were used to combine trials and analyze data. The present review included three studies. In mild to moderate OSA cases, measured using the apnea–hypopnea index (AHI), 50% protrusion was more effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
1
14
2
Order By: Relevance
“…Few other studies which supported our results were the systematic reviews by Kannan et al [24] and Sakamoto et al [25], who found significant increase in pharyngeal airway dimensions with the use of functional appliances.…”
Section: Discussionsupporting
confidence: 88%
“…Few other studies which supported our results were the systematic reviews by Kannan et al [24] and Sakamoto et al [25], who found significant increase in pharyngeal airway dimensions with the use of functional appliances.…”
Section: Discussionsupporting
confidence: 88%
“…In the study by Ringvist et al that used the appliance that provided only posterior occlusal coverage and protruded the mandible, only 50% showed no change in overjet and overbite. On the other hand, a systematic review and meta-analysis found no significant difference between the side effects caused by 50% and 75% of maximum protrusion [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AP protocol aims for individualisation of OA treatment. Standard protocol OA treatment suggests ‘maximal comfortable protrusion’, which often results in 50%‐80% of maximal protrusive range as the target OA position for optimal treatment effect 40,41 . A systematic review investigating clinical practice in OA titration found that all included studies describing percentage of maximal protrusion reported a mean protrusion exceeding 85% 10 .…”
Section: Discussionmentioning
confidence: 99%